2017
DOI: 10.3390/md15080237
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina platensis Improves Mitochondrial Function Impaired by Elevated Oxidative Stress in Adipose-Derived Mesenchymal Stromal Cells (ASCs) and Intestinal Epithelial Cells (IECs), and Enhances Insulin Sensitivity in Equine Metabolic Syndrome (EMS) Horses

Abstract: Equine Metabolic Syndrome (EMS) is a steadily growing life-threatening endocrine disorder linked to insulin resistance, oxidative stress, and systemic inflammation. Inflammatory microenvironment of adipose tissue constitutes the direct tissue milieu for various cell populations, including adipose-derived mesenchymal stromal cells (ASCs), widely considered as a potential therapeutic cell source in the course of the treatment of metabolic disorders. Moreover, elevated oxidative stress induces inflammation in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 76 publications
6
47
0
2
Order By: Relevance
“…Osman et al (2016) showed that Spirulina suspension can also induce the biosynthesis of proteins and amino acids in roots and shoots, which can act as a protector from harmful effect of herbicides. In the work of Nawrocka et al (2017) it was also shown that Spirulina platensis contains also pigment—phycocyanin (266 ± 23 mg 100 g −1 d.m. ), polyphenols, determined with Folin–Ciocalteu reagent (176 ± 5 mg 100 g −1 expressed as equivalents of gallic acid), vitamins such as α-tocopherol (2.43 ± 0.21 mg 100 g −1 ), γ-tocopherol (1.07 ± 0.21 mg 100 g −1 ) and ascorbic acid (18.37 ± 0.97 mg 100 g −1 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Osman et al (2016) showed that Spirulina suspension can also induce the biosynthesis of proteins and amino acids in roots and shoots, which can act as a protector from harmful effect of herbicides. In the work of Nawrocka et al (2017) it was also shown that Spirulina platensis contains also pigment—phycocyanin (266 ± 23 mg 100 g −1 d.m. ), polyphenols, determined with Folin–Ciocalteu reagent (176 ± 5 mg 100 g −1 expressed as equivalents of gallic acid), vitamins such as α-tocopherol (2.43 ± 0.21 mg 100 g −1 ), γ-tocopherol (1.07 ± 0.21 mg 100 g −1 ) and ascorbic acid (18.37 ± 0.97 mg 100 g −1 ).…”
Section: Discussionmentioning
confidence: 94%
“…Cyanobacteria are known to contain a wide variety of compounds, which include 40% of lipopeptides (with cytotoxic (41%), antitumor (13%), antiviral (4%), antibiotics activity (12%) and the remaining 18% activities include anti-malarial, antimycotics, multidrug resistance reversers, antifeedant, herbicides and immunosuppressive agents), 5.6% of amino acids, 4.2% of fatty acids, 4.2% of macrolides and 9% of amides (Singh et al 2008). Spirulina platensis used in the present study is rich in free and bound amino acids, including alanine, glycine, valine, leucine, isoleucine, asparagine, aspartic acid, glutamine, glutamic acid, lysine, arginine, histidine, phenylalanine, tyrosine, tryptophan, serine, threonine, methionine, cysteine and proline (Nawrocka et al, 2017). Osman et al (2016) showed that Spirulina suspension can also induce the biosynthesis of proteins and amino acids in roots and shoots, which can act as a protector from harmful effect of herbicides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies illustrated that Spirulina extracts can stimulate the immune system, improve glucose and lipid metabolism, and prevent or inhibit different types of cancer [12][13][14][15]. Spirulina has also been claimed to prevent chronic diffusion of liver disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…C-phycocyanin (C-PC) seems to play master roles in the hypolipidemic effect of spirulina since it has been found to inhibit jejunal cholesterol absorption 37 and lipase activity 38 .The hypolipidemic effect of Spirulina in our investigation could be referred to its essential polyunsaturated fatty acids as omega-6, omega-3 and linolenic acid and vitamin B3 39 . Moreover, dietary supplementation with C-PC or Spirulina platensis significantly inhibits pro-inflammatory cytokine formation, such as TNF-α, IL-1b and suppresses cyclooxygenase-2 (COX-2) expression induced by the salicylate 40 .…”
Section: Cmentioning
confidence: 67%